Applying Ecological Frameworks in Obesity Intervention Studies in Hispanic/Latino Youth: A Systematic Review. (September 2017) - Kiraly, Carmen; Turk, Melanie T.; Kalarchian, Melissa A.; Shaffer, Cheryl
Introduction: In the United States, Hispanic children have higher rates of obesity compared with non-Hispanic White children. An ecological framework provides a holistic view of the environment to which Hispanic/Latino children are exposed that can potentially inform prevention and treatment initiatives for this vulnerable population. Method: This systematic review examines the existing evidence on the use of an ecological framework in intervention studies targeting overweight and obesity in Hispanic youth from birth to 8 years. Key terms guided the search of PubMed, Google Scholar, CINAHL, and EBSCOhost databases from 1997 to 2016. Results were organized using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) method. Results: Seven studies met the inclusion and exclusion criteria. Significant improvements in body mass index z scores in treatment children were evident in five of the seven studies. Increases in fruit, water, and vegetable consumption and physical activity levels were reported in four of the seven studies. Conclusion: Multilevel interventions targeting a child's home and community suggest efficacy in reducing or preventing obesity; increasing fruit, water, and vegetable consumption; and increasing physical activity in overweight/obese young Hispanic children. Future research is needed to explore the sustainability of multilevel obesity prevention interventions in this vulnerable population.